Influence of humidity on the performance of CH3NH3PbI3-xClx perovskite solar cells - Sia, Rachael Wan-Lyn; Low, Pei-Ling; Thien, Gregory Soon How; Kar, Ban Tan; Ng, Zi-Neng; Marlinda, Ab Rahman; Boon, Kar Yap; Chan, Kah-Yoong (Semarak Ilmu Publishing, 2025)
Perovskite solar cells (PSC) are widely studied due to their high efficiency of up to 25%. Nonetheless, the perovskite material is susceptible to humidity as water can lead to its degradation. Given that the humidity in Malaysia is exceptionally high, significant care must be taken when fabricating the PSC in a low-humidity environment. Therefore, this paper investigated the influence of humidity on the performance of PSCs. A mixed cation CH3NH3PbI3-xClx perovskite ink was used in this study further to eliminate other contributing factors to performance degradation. The fabricated device demonstrated 0.6% power conversion efficiency (PCE) at 50 % relative humidity (RH). In contrast, the PCE was 1% at 30 %RH. Consequently, it is proven that humidity plays an essential role in optimising the PSC, as higher humidity will result in a low performing device. Overall, this study can assist in the future prospects in commercialising perovskite fabrication in Malaysia.